主流中的边缘人﹕从《谁先爱上他的》看华人社会中的同妻形象 = Mainstream outsider : a study of the image of “Tongqi”(Gay Man’s Wife) in Chinese society in Dear Ex - 林佳敏 Lim, Jasmine (Nanyang Technological University, 2021)
同志群体在社会上的能见度已有显著的提升，于华语电影中有越来越多相关的同志题材作品，使得他们得以通过这一媒介再次现身、发声。当中不少的电影内容都围绕着以同志与家庭之间的障碍展开，而当中也出现过同性恋者的妻子（同妻）的角色。近年来华语电影开始相继推出以同妻为主的电影，让不被关注的她们，得以在影视中呈现她们的经历。 同志群体作为主流社会中的弱势群体，而同妻群体更是被放置于社会边缘的位置。同妻的特殊身份使她们的生活更为隐匿，群众对同妻群体的认知也了解甚少。在同志电影研究中，亦鲜有学者对电影中的同妻展开研究。 本文将以台湾同志电影《谁先爱上他的》作为研究对象，借用女性主义、酷儿等相关理论，探讨华人社会的同妻境况与华语电影中相关的同妻角色形象，并进一步探究《谁先爱上他的》中“刘三莲”同妻形象的复杂性。 The social visibility of the LGBTQ ( Lesbian Gay Bisexual Transgender and Queer) community has been significantly improved. The LGBTQ-related themes are more frequently seen in Chinese films, which offer their community greater opportunities to show up and voice out to the public. Many of the films focus on the communication barriers between gay men and their families, which also leads to a greater visibility of “tongqi”（同妻）- gay men’s wives, to be represented in recent films. The experiences of the Gay men’s Wives has become more widely recognized by public, due to the emerge of Chinese films which featuring on Gay’s Wife in recent years. Gay men have been regarded as a minority group within the mainstream society, while their wives were more notably living on the fringe of society. As women in a patriarchal world and wives of gay men, they were double-marginalized and not widely recognized by the public. Among the studies on LBGTQ-related film, there is very limited study of the images of tongqi. This paper aims to perform a close reading on Taiwan are LGBTQ film Dear Ex, by applying theories in feminism and queer studies to discuss the current situation of tongqi in Chinese society and how their images are shown in other Chinese films. This paper will also analyze the character Liu Sanlian in Dear Ex to examine the growing complexity of the image of tongqi in contemporary Chinese cinema.